Analysis of Inelastic Collision π- + C at 915 MeV - Mongelli, S.; Romano, A.; Waloschek, Pedro; Gentile, Antonio; Perez Ferreira, Emma (Societa italiana di fisica, 1962)
Fil: Mongelli, S. Istituto di Fisica dell’ Università, Bari; Italia